PENGEMBANGAN MODEL LATIHAN PASSING PADA PERMAINAN FUTSAL UNTUK ANAK USIA SEKOLAH DASAR - Muhammad Dimas Kartika Fajrin; Dicky Reva Apriana Sanga Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study addresses the problem of limited mastery of basic passing techniques in futsal among elementary school students, which often leads to inaccurate passes and ineffective teamwork during practice and games. The purpose of this research is to develop a passing training model that is suitable for the motor development and learning needs of elementary school children. The research method applied was Research and Development (R&D) using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants were 20 sixth-grade students from SD Negeri Kertaungaran. The product was validated by material experts and futsal practitioners, with the results showing that the developed model fell into the “feasible to very feasible” category, scoring between 80% and 82%. Field implementation involved pretests and posttests to measure the effectiveness of the training. The findings indicated a significant improvement in students’ passing skills, with the mean pretest score of 75.7 increasing to 87 in the posttest. The paired sample t-test confirmed that the improvement was statistically significant (sig. 0.00 < 0.05). Furthermore, student responses reached 90%, categorized as “very feasible,” reflecting that the model was easy to understand, engaging, and aligned with their physical development. In conclusion, the developed passing training model proved effective in enhancing the passing skills of elementary school students. This model can serve as an alternative approach in physical education learning and futsal extracurricular activities to improve the quality of basic futsal skills in children.